2004
DOI: 10.1007/s00223-004-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Ribavirin, but Not Interferon α-2b, is Associated with Impaired Osteoblast Proliferation and Differentiation In Vitro

Abstract: Hepatitis C treatment with interferon alpha-2b (IFN-alpha) and ribavirin has been related to decreased bone mineral density. The aim of this study was to investigate the in vitro effects of different concentrations of ribavirin and IFN-alpha on osteoblast-like cells. Human osteoblast-like cells obtained by the outgrowth of cells from bone chips were exposed to ribavirin (0.1-10 microg/mL) or IFN-alpha (0.1-1000 UI/mL). At regular time-points, cultures were harvested for posterior analysis. Alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
0
15
0
3
Order By: Relevance
“…Trombetti et al [47], on the other hand, did not find any effect of ribavirin in bone metabolism. The impact, therefore, of IFN-alpha and ribavirin in bone remains unclear [48]. In our study, there was no statistically significant difference between patients with hepatitis B received IFN-alpha alone and combination with lamivudine.…”
Section: Discussionmentioning
confidence: 51%
“…Trombetti et al [47], on the other hand, did not find any effect of ribavirin in bone metabolism. The impact, therefore, of IFN-alpha and ribavirin in bone remains unclear [48]. In our study, there was no statistically significant difference between patients with hepatitis B received IFN-alpha alone and combination with lamivudine.…”
Section: Discussionmentioning
confidence: 51%
“…It was also reported that hOB cells provide a useful tool able to help predicting the effects of biomaterials on regenerative capability of periapical tissues (14). It is important to mention that the used cell line has been previously characterized (15).…”
Section: Resultsmentioning
confidence: 99%
“…When human osteoblasts were incubated with ribavirin, a dose-dependent decrease in cell proliferation occurred and there was a significant increase in osteoblast cell death. 88 In contrast, interferon had no effect on osteoblast cell proliferation or death. Other in vitro studies demonstrated that ribavirin directly enhances osteoclast formation, 89 decreases intestinal calcium absorption by directly acting on intestinal mucosa cells, and interferes with 1,25(OH) 2 D production.…”
Section: Effects Of Interferon and Ribavirin On Calcium And Bone Metamentioning
confidence: 97%